Ultrashort Pulse Soliton Fiber Laser Generation With Integration of Antimony Film Saturable Absorber - Rahman, Mohd Fauzi Ab; Latiff, Anas Abdul; Rosol, Ahmad Haziq Aiman; Dimyati, Kaharudin; Wang, Peng Fei; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers, 2018)
A soliton-locked Erbium-doped fiber laser is demonstrated for the first time using a pure Antimony (Sb) film as a saturable absorber (SA). The SA device is fabricated by depositing a 5 μm Sb layer onto a polyvinyl alcohol thin film via Physical vapor deposition process. Self-starting soliton mode-locked pulses train with a constant repetition rate of 0.99 MHz is obtained as the pump power increased from 101 mW to 142 mW. The laser operates at 1559 nm with a pulse width of 3.53 ps. At the pump power of 142 mW, the maximum peak power and pulse energy are calculated as 5.83 kW and 20.59 nJ, respectively. The obtainable pulse is very stable with a signal-to-noise ratio (SNR) of 70 dB. Our experimental results manifest that the pure Sb thin film-based SA is able to generate mode-locked pulsed laser at the 1.55-micron laser regime.